2022
DOI: 10.1039/d1ta09499h
|View full text |Cite
|
Sign up to set email alerts
|

Highly safe and stable lithium–metal batteries based on a quasi-solid-state electrolyte

Abstract: A ZIF-69-SN quasi-solid-state electrolyte enables high safety and stability in lithium–metal batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Cyano groups in SBN could be spontaneously polymerized by the catalytic lithium metal and form harmful by-products. 55 In the disassembled LMB, a brown and thick solid by-product layer was observed on the lithium anode aer cycling (Fig. S13 in the ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…Cyano groups in SBN could be spontaneously polymerized by the catalytic lithium metal and form harmful by-products. 55 In the disassembled LMB, a brown and thick solid by-product layer was observed on the lithium anode aer cycling (Fig. S13 in the ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] Solid-state electrolytes are one of the key ASSB components, because of their ionic conductivity and chemical/electrochemical stability that determine the battery performance. In this context, tremendous research is ongoing to improve the ionic conductivities of oxides, [8][9][10][11][12] suldes, [13][14][15] hydrides, [16][17][18] metal-organic frameworks (MOFs), 19,20 and molecular crystals. [21][22][23] Among the various materials reported to date, complex hydrides have received considerable attention because of their high ionic conductivities, superior electrochemical stabilities, high deformabilities, and low material densities.…”
Section: Introductionmentioning
confidence: 99%
“…Aimed at this, a metal‐organic framework (MOF) with a sieve effect for electrolyte solvation sheaths is chosen to load concentrated SN‐based electrolytes for LMBs. The study shows that the existence of MOF reduces the solvent molecules in the Li + solvation sheath than that of the saturated electrolyte [84a] . And an extended electrochemical stability window of 5.4 V vs. Li/Li + , a high t Li+ of 0.67 and superior compatibility to Li anode (cycle lifespan over 1600 h) have been displayed.…”
Section: The Design and Modification Strategies Of Gel Electrolyte Fo...mentioning
confidence: 90%
“…It has been reported that the intensive polarity of SN enables the enhanced ionic conductivity because of the promoted dissolution of Li salts and the accelerated diffusion of Li + . However, SN is unstable against Li metal because Li metal would catalyze the polymerization of the nitrile groups of SN, resulting in the increase of the interfacial resistance between the SN and Li metal anode [84a] . Aimed at this, a metal‐organic framework (MOF) with a sieve effect for electrolyte solvation sheaths is chosen to load concentrated SN‐based electrolytes for LMBs.…”
Section: The Design and Modification Strategies Of Gel Electrolyte Fo...mentioning
confidence: 99%